2020
DOI: 10.31521/modecon.v19(2020)-12
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Environmental Costs in the Enterprise Management System in Conditions of Sustainable Development

Abstract: Облік екологічних витрат у системі управління підприємством в умовах сталого розвитку Анотація. Стаття присвячена проблемним питанням обліку екологічних витрат у системі управління підприємством в умовах сталого розвитку. Вітчизняне законодавство не надає трактування поняттям «екологічний облік» та «облік екологічних витрат». З огляду на це, ведеться серйозна полеміка між науковцями та фахівцямипрактиками щодо необхідності виокремлення обліку екологічних витрат та відображення його у складі бухгалтерського. Пи… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…By analyzing the converted accounting costing formula, it can be found that Fourier transform integrates the original disorganized costing into a centralized accounting method [18]. Moreover, in this transformation process, based on the excellent characteristics of Fourier transform, some new progress has been made in the centralized accounting method of accounting costs.…”
Section: Centralized Accounting Of Enterprise Accounting Costsmentioning
confidence: 99%
“…By analyzing the converted accounting costing formula, it can be found that Fourier transform integrates the original disorganized costing into a centralized accounting method [18]. Moreover, in this transformation process, based on the excellent characteristics of Fourier transform, some new progress has been made in the centralized accounting method of accounting costs.…”
Section: Centralized Accounting Of Enterprise Accounting Costsmentioning
confidence: 99%
“…The need to adjust the regulatory framework to en sure the specified economic efficiency is pointed out. The ar ticle by Kolisnyk and Gordienko [8] points out the importance of systematization of costs when the enterprise maintains eco logically oriented accounting of environmental costs in the management system, which is also taken into account in this article. Storozhuk and Druzhynska [9] indicated that account ing should provide data for structures of different levels: state, region, branch and enterprise level, which requires the intro duction of a new information system.…”
mentioning
confidence: 99%